The Loss of Agricultural Traditions: A Study of the Social Impact of Mining on Mine-Round Communities - M. Ridha Ajam; Irfan Ahmad; Andi Sumar Karman; Bahtiar Hairullah; Safrudin Abd Rahman (Journal of Social Science, 2023)
This research examines the Loss of Agricultural Traditions: A Study of the Social Impact of Mining on Mine-Round Communities by appointing PT. IWIP as a case study. This appointment is based on the reason that PT. IWIP is the first integrated industrial estate management company in Indonesia. This research is a qualitative research conducted in Weda Tengah District, Central Halmahera Regency, North Maluku Province. The purpose of this study is to explain the Loss of Agricultural Traditions: A Study of the Social Impact of Mining on Mine-Round Communities. The method used in this study is descriptive qualitative with an ethnographic approach. Data collection was carried out through document studies (literature review), observation (observation), and in-depth interviews. Research informants are people who live in the mining area which are determined by purposive sampling based on their knowledge and experience related to the research topic. The results of the study show that the presence of mining companies has a broad impact on people's lives. One of these impacts can be found in social and cultural aspects. Based on their nature, these impacts are positive and negative. If viewed from the perspective of social change, the various descriptions above show that the community in the mining area has experienced changes, whether consciously or not. This social change that occurred at the same time also penetrated the joints of the culture of society that was oriented towards agriculture.